Acute Cardiac Emergencies. Issue 3 (July 2022) - Bucklew, Eric; Noory, Ali; Okumus, Nazli; Radhakrishnan, Srikanth; Mahabir, Sunita; Samra, Gursharan; Dysert, Karen; Cheema, Tariq; Ivanova, Valentyna
Abstract : Acute cardiac emergencies are life threatening. The initial responses to acute cardiac emergencies must be rapid, efficient, skillful, and well-planned. The goal of this article is to provide information that can be used to facilitate the prompt recognition and treatment of the most common acute cardiac emergencies.